Предмет: Алгебра,
автор: demondark2002
если функция задана формулой f(x)=-x^2+3 то запишите формулу функции
а ) f(5х)
б ) f(x-2)
с ) f(7-x)
д ) f(2x+3)
Ответы
Автор ответа:
0
f(5x)=5x^2+3
f(x-2)=(x-2)^2+3
f (7-x)=(7-x)^2+3
f(2x+3)=(2x+3)^2+3
f(x-2)=(x-2)^2+3
f (7-x)=(7-x)^2+3
f(2x+3)=(2x+3)^2+3
Автор ответа:
0
простите впереди должен стоять - как по формуле
Похожие вопросы
Предмет: Физика,
автор: tokiygul228
Предмет: Математика,
автор: psozinov7
Предмет: Математика,
автор: Аноним
Предмет: Химия,
автор: Змееголовый